Comparison of incidence of acute kidney injury following percutaneous coronary intervention between transradial and transfemoral approaches - Saha, Mithun; Uddin, Mir Jamal; Momen, Abdul; Dey, Antara; Datta, Gokul Chandra; Barman, Badal Chandra; Debnath, Deb Dulal (International Journal of Research in Medical Sciences, 2025)
Background: Acute kidney injury (AKI) is a significant complication in percutaneous coronary intervention (PCI) patients. Periprocedural bleeding and vascular access site complications are emerging risk factors for post-PCI AKI. Recent studies suggest that transradial PCI has a lower incidence of AKI compared to transfemoral PCI, attributed to reduced vascular and bleeding complications. This study aimed to compare the incidence of acute kidney injury following PCI between transradial and transfemoral approaches. Methods: This cross-sectional study included 200 ischemic heart disease patients who underwent percutaneous coronary intervention (PCI) via transradial access (TRA, n=98) or transfemoral access (TFA, n=102) from June 2018 to May 2019 at the National Institute of Cardiovascular Diseases (NICVD) Hospital, Dhaka, Bangladesh. Samples were selected purposively, and AKI incidence was assessed post-procedure through serum creatinine levels and urine output. Data analysis was performed using SPSS version 23.0. Results: Demographic and risk factor variables were similar in both groups. Compared to transfemoral approaches (TFA), transradial approaches (TRA) resulted in significantly fewer major bleeding events (0% vs. 4%, p=0.04) and vascular access site complications (p=0.04). TRA was also associated with a lower incidence of AKI post-PCI (2% vs. 8.8%, p=0.03). Multivariate logistic regression identified transfemoral access as the strongest predictor of AKI after PCI (p=0.001). Conclusions: The transradial approach is associated with a lower incidence of acute kidney injury (AKI) following percutaneous coronary intervention (PCI) compared to the femoral approach.